Book Review: Elementary Change: Moving Toward Systemic School Reform in Rural Kentucky - Kristine Reed; Paul Theobald (Journal of Research in Rural Education, 2001)
Elementary Change is a report on research conducted by the authors over an extended period-10 years, in fact-although the bulk of the volume reports on work conducted between 1996 and 1999. It is, essentially, an evaluation study purported to answer four key questions related to Kentucky's implementation of the court-mandated Kentucky Educational Reform Act (KERA) of 1990: Did KERA help all students achieve specified, high level outcomes? Did teachers change their curriculum, instructional approaches, and assessment strategies? Did schools take on the burden of educational decision-making? Did the implementation of an innovative "primary program" help the state's schools achieve KERA goals?